2022
DOI: 10.24114/cess.v7i2.37336
|View full text |Cite
|
Sign up to set email alerts
|

Epoch Optimization on Rice Leaf Image Classification Using Convolutional Neural Network (CNN) MobileNet

Abstract: Epoch pada proses klasifikasi citra menggunakan algoritma deep learning convolutional neural network (CNN) merupakan proses yang mutlak dibutuhkan untuk mencapai akurasi paling optimal dan loss yang kecil. Penentuan epoch akan mempengaruhi bobot (weight) pada neural network serta berpengaruh pada kurva yang dihasilkan. Proses training dataset citra pada neural network akan melalui satu rangkaian perhitungan dari awal sampai akhir hingga akan dikembalikan lagi ke proses awal dengan sebutan sekali putaran atau 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Similarly, in a study of tomato seed variety classification, the MobileNet model achieved the highest classification accuracy [8]. In a study of rice plant leaf classification, the MobileNet model, with 150 epochs, resulted in the highest accuracy [9]. These findings highlight the effectiveness of the MobileNet model in various image classification tasks.…”
Section: Introductionmentioning
confidence: 75%
“…Similarly, in a study of tomato seed variety classification, the MobileNet model achieved the highest classification accuracy [8]. In a study of rice plant leaf classification, the MobileNet model, with 150 epochs, resulted in the highest accuracy [9]. These findings highlight the effectiveness of the MobileNet model in various image classification tasks.…”
Section: Introductionmentioning
confidence: 75%
“…Similarly, in a study of tomato seed variety classification, the MobileNet model achieved the highest classification accuracy [9]. In a study of rice plant leaf classification, the Mobilenet model with 150 epochs resulted in the highest accuracy [10]. These findings highlight the effectiveness of the Mobilenet model in various image classification tasks.…”
Section: Introductionmentioning
confidence: 82%
“…The file is then saved to an SMC card on the computer where the model was taught. This card is transferred to the NPU module and, following the steps suggested by the manufacturer, the S7-1500 family PLC reads the parameters from the card [see Figures 9,10…”
Section: Verification Model Inception On Plcmentioning
confidence: 99%
“…An experiment on the best epoch was carried out by Fauzan in 2022 which stated that the higher the epoch value, the better the accuracy and the smaller the loss. Research on the epoch was carried out with variations of 50, 100 and 150 and the results showed that epoch 150 got the best score (Defriani & Jaelani, 2022;Masykur et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%